Dendritic Cells: A Spot on Sialic Acid - Crespo, Hélio (2013)
This work was supported by the Portuguese Foundation for Science and Technology (FCT) - PTDC/SAU-MII/67561/2006 and CEDOC (Paula A. Videira) and SFRH/BD/61204/2009 (He lio J. Crespo). FCT is co-financed by European Social Fund (ESF) under Human Potential Operation Program (POPH) from National Strategic Reference Framework (NSRF).